Economic Threshold Levels for Signal Grass Control in Sugarcane Cultivars - TIRONI,S.P. (2016)
ABSTRACT Weed management in sugarcane fields must be performed rationally, taking into consideration the competitive ability of cultivars and weeds, to allow for reductions in control costs and herbicide use. In this study, an evaluation was made of the interference of populations of Brachiaria brizantha in sugarcane cultivars, with the objective of estimating the economic threshold level of B. brizantha in competition with the cultivars RB72454, RB867515 and SP801816. For this purpose, an experiment was conducted under field conditions, where the cultivars coexisted with different weed densities. Considering the average values of the variables used for calculations, an economic threshold level was achieved with a population of 0.33, 0.46 and 0.66 plants m-2 of B. brizantha for cultivars RB867515, RB72454 and SP801816, respectively.